Pengaruh Media Edukasi SEHATI Terhadap Pengetahuan Remaja Tentang Seks Edukasi Di SMPN 3 Kota Kediri - Nur Hidayati; Rahajeng Siti Nur Rahmawati; Finta Isti Kundarti; Ira Titisari; Ririn Indriani (Akademi Keperawatan Yarsi Samarinda, 2026)
Adolescents' knowledge regarding sex education remains low, posing a risk of misunderstandings and behaviors that could impact reproductive health. One effort to improve adolescents' knowledge is through the SEHATI / Sex Education: Adolescents' Hope to Avoid Risks) educational medium, presented in the form of an educational video. Objective: To determine the effect of the SEHATI educational medium on adolescents' knowledge levels regarding sex education at SMPN 3 Kediri City in 2026. Methods: This study employed a quantitative method with a pre-experimental design, specifically the One-Group Pretest-Posttest design. The study sample consisted of 78 seventh-grade students from SMPN 3 Kediri City. Data were collected using a knowledge questionnaire administered before and after the SEHATI educational intervention. Data analysis was performed using the Shapiro-Wilk normality test and the Wilcoxon Signed-Rank Test, with a significance level of 0.05. Results: Prior to the SEHATI intervention, the majority of respondents fell into the